KESIAPAN KOTA PEKALONGAN MENUJU SMART CITY - Christianto, Paminto Agung; Nuhayati, Siti; Mujiyono, Mujiyono (BAPPEDA Kota Pekalongan, 2016)
THE CITY HAS A PROBLEM THAT CONTINUES TO GROW IN THE SPATIAL ARRANGEMENT OVER TIME. IT IS NOT UNCOMMON PROBLEMS THAT ARISE DUE TO THE CONSTRUCTION OF HIS OWN CITY. TO BE ABLE TO PREVENT THAT CITY MANAGEMENT IS NEEDED THROUGH A SUSTAINABLE APPROACH TO THE CONCEPT OF PLANNING. AND IS CURRENTLY DEVELOPING THE CONCEPT OF INTELLIGENT CITY AND ONE OF THE MOST IMPORTANT DIMENSIONS OF THE SMART CITY IS THAT THE CITY SHOULD PROVIDE A SERVICE THAT USES THE LATEST TECHNOLOGY AND SMART BUILDING INFRASTRUCTURE, SO AS TO PROVIDE EFFECTIVE SERVICES AND THE COST TO THE PEOPLE LIVING IN THE CITY. TICK INVOLVEMENT IN PEKALONGAN CITY BUILDING HAS BEEN GOING WELL, IT IS SEEN FROM SUPPORT FOR POLICY AND REGULATION OF PEKALONGAN CITY GOVERNMENT AND VARIOUS RELATED AWARDS RECEIVED TIK PEKALONGAN CITY GOVERNMENT BOTH REGIONALLY AND NATIONAL LEVEL. EMPOWERMENT COMPONENT OF THE COMMUNITY THROUGH VOLUNTEER BOARD TIK TIK AND ALSO DELIVER GREAT RESULTS TO ENCOURAGE PEOPLE TO BE LITERATE PEKALONGAN CITY TICK. TO DETERMINE THE LEVEL OF READINESS OF PEKALONGAN CITY TOWARDS THE IMPLEMENTATION OF SMART CITY CONCEPT, THE RIGHT STRATEGY CAN BE PROPOSED TO THE CITY GOVERNMENT SO THAT IT CAN BE REALIZED PEKALONGAN PEKALONGAN SMART CITY THAT CAN PROVIDE SERVICES EFFECTIVELY AND EFFICIENTLY AND PROVIDE COMFORT FOR THE PEOPLE LIVING IN THE TOWN OF PEKALONGAN.